Breeding results for Echinacea purpurea (L.) Moench in Moscow Province - I. N. Korotkikh; E. Yu. Babaeva; A. E. Burova (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. Echinacea purpurea (L.) Moench is a perennial herbaceous plant of the family Asteraceae introduced from North America. Preparations from crude herbal materials of E. purpurea have a widerange effect against pathologies of the immune system, infectious and inflammatory diseases of the respiratory tract, genitourinary system and musculoskeletal system. Breeding work involving E. purpurea has been carried out at the All-Russian Research Institute of Medicinal and Aromatic Plants (Moscow Province) since 1996 with the aim of developing varieties adapted to the regional environments of Central Russia as well as increasing the yield and quality of raw materials by breeding methods. Objects and methods. In the process of breeding in 2009–2016, the collection material of E. purpurea was propagated vegetatively in the field, while the breeding material was reproduced by sowing and transplanting techniques from the seeds obtained under controlled pollination conditions. In the control nursery of the 2nd–5th years of vegetation, accessions promising for breeding were studied and evaluated by comparing them with the reference (var. ‘Tanyusha’). Breeding accessions (Nos. 1-09, 2-09 and 22-09) were obtained by individual selection based on the biological collection of VILAR (Nos. 79, 80 and 38) received in 1998 from the UK (Exchange Seed Fund). Seeds were sown into plots (total area of 9.6 m2 ) with a 4-fold replication. The yield of crude herbal materials (above-ground part) was registered at the beginning of the flowering phase (the first 10 days of August), and fresh and dry mass of the accessions were measured (after 48-hour ventilated drying at 45°C). Chemical analysis of crude herbal materials was made to find the sum of the derivatives of oxycinnamic acids calculated as chicoric acid using chromatic spectrophotometric techniques according to Temporary Pharmacopoeial Article 42-2371-94 and Private Pharmacopoeial Article in State Pharmacopoeia XIII. Results. According to the results of competitive variety trials in 2014–2016, the breeding accessions reliably exceeded the reference ‘Tanyusha’ in a set of economically valuable parameters: in crude herb yield by 10–27%; in the content and total harvest of active substances in crude herb materials by 7–18% and 21–80%, respectively; and in seed yield by 35–47%. Breeding accessions demonstrated normal adaptability to regional conditions (duration of the growing season was 174–176 days, and winter hardiness reached 89–94%). Conclusion. Accession No. 1-09, the best according to a set of economically valuable and biological traits as the results of competitive variety trials have shown, has been submitted to the State Variety Trials as a new cultivar of E. purpurea under the name ‘Severyanka’.